Discretized model for partially shaded PV arrays composed of PV panels with overlapping bypass diodes. (15th November 2017) - Díaz-Dorado, Eloy; Cidrás, José; Carrillo, Camilo
Highlights: PV panels with overlapping diodes are analyzed. A PV array model for partially shaded conditions is presented. The method is based on piecewise polynomial functions obtained by discretization. The proposed method analyzes series and parallel associations. The proposed method includes the models for PV cells, blocking diodes and by-pass diodes. Abstract: There are two typical configurations of bypass diodes used in PV-cell connection: nonoverlapped and overlapped. This paper presents a generalized method for electrical modeling of PV panels with overlapping bypass diodes to analyze nonuniform irradiance situations. The proposed model is based on piecewise polynomial functions, which use a discrete set of data to model PV cells under several shading situations and bypass diode connections. Analyzing electrical connections, the remaining PV array elements are modeled. In the case of a single PV panel, a Newton–Raphson method is used to derive its piecewise polynomial functions. The proposed method is used to provide a complete analysis of current, voltage, and power in PV arrays under partial shading conditions. From the results, it was verified that some elements of a PV array can act as loads under nonuniform irradiance.